The general solution of the differential equation 𝑦𝑑π‘₯ − π‘₯𝑑𝑦 = 0 ; (Given x,y >0)  is of the form

(a) π‘₯𝑦 = 𝐢   (b) π‘₯ = γ€–Cyγ€—^2  (c) 𝑦 = 𝐢π‘₯   (d) 𝑦 = Cx^2

(Where ‘c’ is an arbitrary positive constant of integration)

This question is exactly same as Question-15 CBSE Class 12 Sample Paper for 2023 Boards

Please check


Go Ad-free
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.